Game usability : advice from the experts for advancing the player experience - Isbister, Katherine, 1969-; Schaffer, Noah, ....- (San Francisco, Calif. : Morgan Kaufmann ; Oxford : Elsevier Science [distributor], 2008)
Usability-the ease with which people can use a program to achieve their goals-is a topic of growing interest to game developers. Until now, no comprehensive survey of usability and user research issues and tactics specific to games has been available. This book includes introductions to basic and advanced methods, and advice for evangelizing usability within game studios and publishing houses.
Keywords: Computer games -- Design; Computer games -- Programming